Due pesi e due misure: differenze di genere nella Malattia di Alzheimer - Notaro, Patrizia; Pantano, Pietro; Passarino, Giuseppe; Bruni, Amalia C. (My University, 2017)
Starting from the particular female exposure to Alzheimer’s disease (AD), the aim of the study was to investigate gender differences in the onset and evolution. 1925 medical records of AD patients, diagnosed with NINCDS-ADRDA criteria, were digitalized in order to extrapolate data. The mean age of the sample was 71 years, 57 years for early onset patients and 75 years for late onset, with duration of the disease around 9 years. Data taken into account and differentiated for gender were: prevalence and onset of the disease; time elapsed between the onset and the first visit, the duration of follow-up and the duration of disease; the educational level, cardiovascular and metabolic risk factors. MMSE score was considered at T0 (first visit), T1 (2yrs>T0) and T2 (4yrs>T0). A checklist of symptoms and signs, extrapolated from the cognitive-behavioral anamnesis, was then analyzed. It was furthermore calculated the genotype frequency and the allele frequency on a sample of 912 patients. IBM SPSS 20 statistics software was used (significance was given by p <0.05). Results highlighted that women were more represented in the cohort (67.1%) and in the early onset group (81.6%, p=0.008). There was no gender differences in the time elapsed from symptoms onset to the first visit (4 years), in the follow-up period (4 years) and in the duration of disease (9 years). Women were more cognitively impaired at T0 with 15.9+5.9 MMSE score vs 17+6.5 male score, while men seemed to decline faster at T2, -3.85+4.66 vs -2.93+4.39. Women had a lower level of education 5.6 years vs 6.51 years of men (p=0.000) and presented a higher comorbidity: dysthyroidism (p=0.000), cholesterol (p=0.000) hypertension (p=0.000) and a higher incidence of depression (p=0.000) while men were more statistically represented for irritability (p=0.000). Signs extrapolated from the cognitive-behavioral anamnesis have revealed a higher percentage of man for language impairment (p=0.000), behavioral symptoms (p=0.009), apraxia (p=0.005), spatial disorientation (p=0.006) and calculus impairment (p=0.035). APOE results were not representative in terms of gender differences but confirmed a possible impact of the allele ε4 on cognitive decline. Results have outlined a female patient highly represented in the sample, less educated, with a worse cognitive impairment and more exposed to comorbidity. Men seemed to impair faster in the first 2 years from onset, presenting a more aggressive picture. Furthermore, the diagnosis of the disease for the entire cohort delays of 3 years compared to the international and national mean of time elapsed from onset to first visit, which is about only 1 year The particular exposure of women to dementia and the different evolutionary impact of neurodegenerative diseases, from a gender point of view, still require ample studies and in-depth observations. In particular, the identification of specific gender aspects may be a valuable aid for a more timely identification of diseases and their better management.
Dottorato di Ricerca in Scienze ed Ingegneria dell'Ambiente, delle Costruzioni e dell'Energia. Ciclo XXIX
Keywords: Malattia di Alzheimer; Demenza